Pengaruh Financial Literacy dan Risk Tolerance Terhadap Keputusan Investasi Pada Generasi Z di Kabupaten Bandung Barat - Nursinta, Noviyanti; Handayani, Rini (Peneliti.net, 2025)
This study aims to examine the influence of financial literacy and risk tolerance on investment decisions among Generation Z in West Bandung Regency. The research employs a quantitative approach using multiple linear regression analysis. The findings indicate that the financial literacy level of Generation Z falls into the